2014
DOI: 10.5194/acp-14-471-2014
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of cloud condensation nuclei concentration from aerosol optical quantities: influential factors and uncertainties

Abstract: Abstract. Large-scale measurements of cloud condensation nuclei (CCN) are difficult to obtain on a routine basis, whereas aerosol optical quantities are more readily available. This study investigates the relationship between CCN and aerosol optical quantities for some distinct aerosol types using extensive observational data collected at multiple Atmospheric Radiation Measurement (ARM) Climate Research Facility (CRF) sites around the world. The influences of relative humidity (RH), aerosol hygroscopicity (f R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 68 publications
(80 reference statements)
3
92
3
Order By: Relevance
“…In this context, it is also noteworthy to mention that Liu and Li (2014) showed that the product of σ × AE (denoted as Aerosol Index AI, introduced by Nakajima et al, 2001) provides a better correlation with n CCN than n CCN with σ . By using AI instead of σ in the correlation, Liu and Li (2014) consider information on the aerosol type and the related size distribution (high AI for fine-mode-dominated aerosol, low AI for coarse-mode-dominated aerosol conditions).…”
Section: Leipzig and Limassol Long-term Observations Of Mixed Aerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is also noteworthy to mention that Liu and Li (2014) showed that the product of σ × AE (denoted as Aerosol Index AI, introduced by Nakajima et al, 2001) provides a better correlation with n CCN than n CCN with σ . By using AI instead of σ in the correlation, Liu and Li (2014) consider information on the aerosol type and the related size distribution (high AI for fine-mode-dominated aerosol, low AI for coarse-mode-dominated aerosol conditions).…”
Section: Leipzig and Limassol Long-term Observations Of Mixed Aerosolsmentioning
confidence: 99%
“…Former studies indicate also that measured aerosol optical properties (at wavelengths around 500 nm) can be used to estimate CCN number concentrations, CCNC (Ghan and Collins, 2004;Ghan et al, 2006;Andreae, 2009;Jefferson, 2010;Liu and Li, 2014;Shinozuka et al, 2015).…”
Section: R E Mamouri and A Ansmann: Lidar Profiling Of Ccn-and Inpmentioning
confidence: 99%
“…Moses Eterigho Emetere 1 atmosphere. This process is called aerosol retention, which is quite interesting and cannot be generalized because of its dynamic properties.…”
Section: Systemic Study Of Aerosol Loading and Retention Over Praia-cmentioning
confidence: 99%
“…Liu et al [1] affi rmed that atmospheric aerosols can increase the heat fl ux over the earth. Verheggen and Weijers [2] clarifi ed that aerosols cause cooling while black carbon aerosol causes warming.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the correlation of AOD with CCN number concentrations, a key assumption in this approach, is strongly dependent on ambient relative humidity and aerosol types. Furthermore, these correlations become less reliable when sea salt and mineral dust constitute an important fraction of the particle number, a situation which can be relevant over the ocean or deserts (Liu and Li, 2014). This makes in-situ measurements indispensable 30 and therefore numerous studies of CCN activity have been carried out in a variety of environments, ranging from remote marine over continental background to urban locations, and in the laboratory (e.g., Andreae, 2009a;Asmi et al, 2012; Atmos.…”
Section: Introductionmentioning
confidence: 99%